Race, Climate, and Turnover: An Examination of the Teacher Labor Market in Rural Georgia. (February 2021) - Williams, Sheneka M.; Swain, Walker A.; Graham, Jerome A.
Teacher turnover across the country presents a persistent and growing challenge for schools and districts, with the highest rates of turnover geographically concentrated in the American South. Research on teacher staffing and turnover problems consistently highlight two subsets of schools as struggling to attract and retain well-credentialed, effective educators—predominantly Black schools and rural schools. However, research has rarely explicitly examined the schools that meet both these criteria. We use administrative records and unique climate survey data from Georgia to examine how the intersecting roles of race, money, and school climate shape evolving teacher turnover patterns in rural schools. Findings suggest that while teacher mobility is generally less common in rural schools, considerable inequities exist within the rural space, with majority Black rural schools bearing far more of the brunt of rural teacher turnover. Among rural teachers, Black teachers have higher mobility rates—more likely to make interdistrict moves and to exit rural settings for teaching opportunities in urban and suburban contexts. However, in majority-Black rural schools, higher salaries and school climate factors, such as relational climate and parental involvement, were strong predictors of retention, even after controlling for a rich set of covariates.